Postoperative treatment after partial nail ablation of ingrown toenails - does it matter what we recommend? A blinded randomised study - S. V. Bernardshaw; Liv Helene Dolva Sagedal; Kristin Møystad Michelet; Christina Brudvik (Taylor & Francis Group, 2019)
Trial design: In this blinded randomized study we analyzed patient reported outcome of three different treatments after nail surgery. We compared daily footbath with either alkaline or acidic soap or just a simple bandage of gauze dressing. Method: After partial nail ablation surgery, patients were randomized into three postoperative treatment modalities. Outcome in terms of reduction in pain, improvement of function, reduction of signs of infection and postoperative soothing effect were reported after one and two weeks. A generalized linear mixed model was used to analyze possible statistical differences between the groups. Results: 97 patients, 57% women, mean age 31 years, were included. Men reported significantly less pain and better function than women. Despite a registered lower growth of invasive pathogenic microbes following the use of acidic soaps, this did not lead to less infections than in the groups using either alkaline soap baths or bandaging. On the contrary, patients keeping the bandage on had significantly lower signs of infection after one week. Two patients using soap baths had growth of MRSA. Two weeks postoperatively, all three treatment alternatives had similar patient reported outcome in all parameters, and nobody needed antibiotics. Conclusions: This prospective randomized study was unable to prove that footbath with either acidic or alkaline soap should be preferred to just leave the postoperative bandage on for a week after partial nail ablation. We recommend that postoperative advice should be given on an individual basis, especially since our study did not involve patients with high risk of infections.